Organizações indígenas e as estratégias para a gestão do território - uma análise a partir do consórcio dos produtores - Almeida, Jean Reis de (2021)
In the present study, we reflected on the organization of the Sateré-Mawé people around the sale of products derived from the biodiversity of the Andirá-Marau Indigenous Land, which are intrinsically linked to the culture of that people. According to the National Indian Foundation - FUNAI (2018), the Consortium of Sateré-Mawé Producers (CPSM), includes 450 registered indigenous producers and 306 suitable for the commercialization of guaraná, being responsible for the regulation and assistance of cultivation, management and commercialization of production, in addition to financing the autonomous administration of the Indigenous Territory. The consortium is considered by the indigenous leaders as the “economic arm of the Sateré-Mawé nation”, being articulated and organized in the General Council of the Sateré-Mawé Tribe. The research had as objective to analyze the creation of the Consortium, as well as to know the products of the nature commercialized by the natives and, still, the contextualization of the warana, that has cultural value for the referred people. The research methodology consisted of a qualitative approach, due to its relevance to the studies of social relations and the pluralization of the spheres of life that makes it possible to directly analyze the individual, the group or an institution. Among the research findings, we highlight a type of commercialization with a purpose different from the capitalist mode of production, because according to the reports of the Sateré-Mawé leaders, the products offered for sale represent cultural and identity resistance, being a strategic way of placing imbued products on the market. of cultural value that mobilize actions around policies to protect the territory, preserve biodiversity, generating a cultural economy for the well-being of the indigenous people.